DARI PLURALITAS KE SINGULARITAS: HISTORIOGRAFI PERKEMBANGAN INTERIOR ARSITEKTUR BALI DARI ERA BALI KUNO SAMPAI AWAL ABAD KE-20 - Noorwatha, I Kadek Dwi (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
This paper attempts to describe the historiography of Balinese interior architecture from Bali Kuno era to early 20th century in a nutshell. The method used is the historical method using primary sources that are close to his time, both foreign and local literature.